2014
DOI: 10.4161/19420862.2014.975658
|View full text |Cite
|
Sign up to set email alerts
|

Resolving self-association of a therapeutic antibody by formulation optimization and molecular approaches

Abstract: (2014) Resolving selfassociation of a therapeutic antibody by formulation optimization and molecular approaches, mAbs, 6:6, 1533-1539, DOI: 10.4161/19420862.2014 To link to this article: https://doi.org/10. 4161/19420862.2014 A common challenge encountered during development of high concentration monoclonal antibody formulations is preventing self-association. Depending on the antibody and its formulation, self-association can be seen as aggregation, precipitation, opalescence or phase separation. Here we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…2 In recent years, LLPS challenges during the formulation development of multiple mAbs or mAb derivatives have been described in the literature. [1][2][3][4][5][6] Several of the reports propose that the progression to, and final equilibrium state of, LLPS are dictated by physicochemical conditions, such as temperature, pH, ionic strength, buffering agents, and the type and concentration of other excipients. [3][4][5] MAbs are effective therapeutics for numerous pathological conditions, including cancer, inflammation, infectious diseases, autoimmune diseases, and neurological disorders.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…2 In recent years, LLPS challenges during the formulation development of multiple mAbs or mAb derivatives have been described in the literature. [1][2][3][4][5][6] Several of the reports propose that the progression to, and final equilibrium state of, LLPS are dictated by physicochemical conditions, such as temperature, pH, ionic strength, buffering agents, and the type and concentration of other excipients. [3][4][5] MAbs are effective therapeutics for numerous pathological conditions, including cancer, inflammation, infectious diseases, autoimmune diseases, and neurological disorders.…”
Section: Introductionmentioning
confidence: 99%
“…LLPS is often considered a manageable challenge for downstream processing with the majority of the reported LLPS cases today arising from formulation development, particularly for mAbs requiring high concentration formulation. [1][2][3][4][5][6] Luo et. al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…19,20 Multiple publications have demonstrated that the amino acid sequence of the constant and variable regions of antibodies can affect molecular stability, expression levels, downstream processing conditions, and formulation conditions required for stable longterm storage. [19][20][21][22][23][24][25][26][27] Clark et al 20 demonstrated that introduction of multiple amino acid substitutions into the Fv region of an IgG2 to alter the amount of exposed hydrophobic and hydrophilic surface areas resulted in an increased titer that correlated with an increase in the thermal stability of the variants. Pettit et al 22 inserted a missing Lys residue at position 148 of the light chain (LC) for an anti-ebola antibody and demonstrated a significant increase in titer, reduction in high-molecular-weight (HMW) species, and increase in thermal stability by differential scanning fluorimetry (DSF) from material produced by stable CHO cell lines as compared to the parental material demonstrating the importance of primary sequence in expressions and biophysical properties of an antibody.…”
Section: Introductionmentioning
confidence: 99%